Effect of Rapid Influenza Diagnostic Testing on Antiviral Treatment Decisions for Patients with Influenza-like Illness: Southwestern U.S., May–December 2009. (July 2014) - Suryaprasad, Anil; Redd, John T.; Ricks, Philip M.; Podewils, Laura Jean; Brett, Meghan; Oski, Jane; Minenna, Wanda; Armao, Frank; Vize, Barbara J.; Cheek, James E.
Rapid influenza diagnostic tests (RIDTs) had low test sensitivity for detecting 2009 pandemic influenza A (H1N1pdm09) infection, causing public health authorities to recommend that treatment decisions be based primarily upon risk for influenza complications. We used multivariate Poisson regression analysis to estimate the contribution of RIDT results and risk for H1N1pdm09 complications to receipt of early antiviral (AV) treatment among 290 people with influenza-like illness (ILI) who received an RIDT ≤48 hours after symptom onset from May to December 2009 at four southwestern U.S. facilities. RIDT results had a stronger association with receipt of early AVs (rate ratio [RR] = 3.3, 95% confidence interval [CI] 2.4, 4.6) than did the presence of risk factors for H1N1pdm09 complications (age <5 years or high-risk medical conditions) (RR=1.9, 95% CI 1.3, 2.7). Few at-risk people (28/126, 22%) who had a negative RIDT received early AVs, suggesting the need for sustained efforts by public health to influence clinician practices.